(untitled) (REVISTA NODO, 2024)
From the University of Barcelona, the research centers Art Globalization and Interculturality (AGI) and Global Art Archive (GAA) have promoted numerous studies of contemporary Latin American art. In this context, the article evaluates to what extent this has represented an ordinary example of cadre training or, on the contrary, there are sufficient nuances to recognize the experience as an episode of redistribution of knowledge.